2020
DOI: 10.5469/neuroint.2019.00213
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy for Venous Malformations of Head and Neck: Systematic Review and Meta-Analysis

Abstract: We performed a systematic review and meta-analysis of studies performing sclerotherapy for treatment of venous malformations (VMs) of the face, head and neck. It is our hope that data from this study could be used to better inform providers and patients regarding the benefits and risks of percutaneous sclerotherapy for treatment of face, head and neck VMs. We searched PubMed, MEDLINE, and EMBASE from 2000–2018 for studies evaluating the safety and efficacy of percutaneous sclerotherapy of neck, face and head V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…In China, the most used method for venous malformations is the well-known antineoplastic agent pingyangmycin, applied as local injection therapy (19). Pingyangmycin has a chemical structure similar to bleomycin A5, and because of its safety, convenience, rapid and effective characteristics, intralesion injection of pingyangmycin has been widely used in the treatment of oral and maxillofacial-head and neck venous malformations (20). Studies have shown that the main mechanisms of pingyangmycin in the treatment of venous malformations sees pingyangmycin bind with vascular endothelial cell DNA causing DNA strand breakage and inhibition of the metabolism of vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the most used method for venous malformations is the well-known antineoplastic agent pingyangmycin, applied as local injection therapy (19). Pingyangmycin has a chemical structure similar to bleomycin A5, and because of its safety, convenience, rapid and effective characteristics, intralesion injection of pingyangmycin has been widely used in the treatment of oral and maxillofacial-head and neck venous malformations (20). Studies have shown that the main mechanisms of pingyangmycin in the treatment of venous malformations sees pingyangmycin bind with vascular endothelial cell DNA causing DNA strand breakage and inhibition of the metabolism of vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…64 Regarding the head and neck lesions, as the most common localization, the possibility of swelling after sclerotherapy has to be considered, potentially requiring protective intubation for a few days. 65 However, this complication should be generally possible to avoid if the procedure is performed carefully and with consideration of distinct high-risk locations 66 67 (e.g., the tongue and the pharynx). The latter can pose even more clinical challenges: due to mucosal involvement, the tongue surface may be very susceptible to infection, bleeding, as well as irritation during feeding.…”
Section: Interventional Treatment Optionsmentioning
confidence: 99%
“…Three genes ( KRIT1 , CCM2 , and PDCD10 ) are known to cause familial CCM [ 39 ]. Venous malformation (VM) is relatively common in head and neck areas, which shows a good response to sclerotherapy [ 40 41 42 ]. Its prevalence or genetic association has not been well-recognized in Korea.…”
Section: Composition Of An Rnvd Panel and Prevalence Of Each Disease In Koreamentioning
confidence: 99%